+0

# Find the 5th term of the expansion of the binomial (3x-1) 7

0
411
3

Find the 5th term of the expansion of the binomial (3x-1)7

Guest Mar 1, 2017
Sort:

#1
0

Find the 5th term of the expansion of the binomial (3x-1)7

The 5th term =3^3 x binomial(7, 4) x^3 =945 x^3.

Guest Mar 1, 2017
#2
+79894
0

The 5th term will be given by :

C(7, 4) (3x)^3 * (1)^4  =    35 * 27 * x^3   =  945 x^3

CPhill  Mar 1, 2017
#3
+18777
+5

Find the 5th term of the expansion of the binomial (3x-1)7

$$\begin{array}{|rcll|} \hline (3x-1)^7 &=& \binom{7}{0}\cdot (3x)^7 + \binom{7}{1}\cdot (3x)^6\cdot(-1)^1 \\ &+& \binom{7}{2}\cdot (3x)^5\cdot(-1)^2 + \binom{7}{3}\cdot (3x)^4\cdot(-1)^3 \\ &+& \color{Maroon}\binom{7}{4}\cdot (3x)^3\cdot(-1)^4\color{black} + \binom{7}{5}\cdot (3x)^2\cdot(-1)^5 \\ &+& \binom{7}{6}\cdot (3x)^1\cdot(-1)^6 + \binom{7}{7}(-1)^7 \\ \hline \end{array}$$

The 5th term of the binomial (3x-1)is:

$$\begin{array}{|rcll|} \hline && \color{Maroon}\binom{7}{4}\cdot (3x)^3\cdot(-1)^4\color{black} \\ &=& \binom{7}{4}\cdot (3x)^3 \quad & | \quad \binom{7}{4} = \binom{7}{7-4} = \binom{7}{3} \\ &=& \binom{7}{3}\cdot (3x)^3 \\ &=& \binom{7}{3}\cdot 27x^3 \\ &=& \frac{7}{3}\cdot\frac{6}{2}\cdot\frac{5}{1}\cdot 27x^3 \\ &=& 7\cdot\frac{6}{6}\cdot 5\cdot 27x^3 \\ &=& 35\cdot 27x^3 \\ &\mathbf{=}& \mathbf{945x^3} \\ \hline \end{array}$$

heureka  Mar 1, 2017

### 17 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details